The Abscission Checkpoint: A Guardian of Chromosomal Stability - Eleni Petsalaki; George Zachos (Cells, 2021)
The abscission checkpoint contributes to the fidelity of chromosome segregation by delaying completion of cytokinesis (abscission) when there is chromatin lagging in the intercellular bridge between dividing cells. Although additional triggers of an abscission checkpoint-delay have been described, including nuclear pore defects, replication stress or high intercellular bridge tension, this review will focus only on chromatin bridges. In the presence of such abnormal chromosomal tethers in mammalian cells, the abscission checkpoint requires proper localization and optimal kinase activity of the Chromosomal Passenger Complex (CPC)-catalytic subunit Aurora B at the midbody and culminates in the inhibition of Endosomal Sorting Complex Required for Transport-III (ESCRT-III) components at the abscission site to delay the final cut. Furthermore, cells with an active checkpoint stabilize the narrow cytoplasmic canal that connects the two daughter cells until the chromatin bridges are resolved. Unsuccessful resolution of chromatin bridges in checkpoint-deficient cells or in cells with unstable intercellular canals can lead to chromatin bridge breakage or tetraploidization by regression of the cleavage furrow. In turn, these outcomes can lead to accumulation of DNA damage, chromothripsis, generation of hypermutation clusters and chromosomal instability, which are associated with cancer formation or progression. Recently, many important questions regarding the mechanisms of the abscission checkpoint have been investigated, such as how the presence of chromatin bridges is signaled to the CPC, how Aurora B localization and kinase activity is regulated in late midbodies, the signaling pathways by which Aurora B implements the abscission delay, and how the actin cytoskeleton is remodeled to stabilize intercellular canals with DNA bridges. Here, we review recent progress toward understanding the mechanisms of the abscission checkpoint and its role in guarding genome integrity at the chromosome level, and consider its potential implications for cancer therapy.